Consensus Guidelines of Irreversible Electroporation for Pancreatic Tumors: Protocol Standardization Using the Modified Delphi Technique - Vos, Danielle J. W.; Ruarus, Alette H.; Timmer, Florentine E. F.; Geboers, Bart; Bagla, Sandeep; Belfiore, Giuseppe; Besselink, Marc G.; Leen, Edward; Martin II, Robert C. G.; Narayanan, Govindarjan; Nilsson, Anders; Paiella, Salvatore; Weintraub, Joshua L.; Wiggermann, Philipp; Scheffer, Hester J.; Meijerink, Martijn R. (Seminars in Interventional Radiology, 2024)
Since no uniform treatment protocol for pancreatic irreversible electroporation (IRE) exists, the heterogeneity throughout literature complicates the comparison of results. To reach agreement among experts, a consensus study was performed. Eleven experts, recruited according to predefined criteria regarding previous IRE publications, participated anonymously in three rounds of questionnaires according to a modified Delphi technique. Consensus was defined as having reached ≥80% agreement. Response rates were 100, 64, and 64% in rounds 1 to 3, respectively; consensus was reached in 93%. Pancreatic IRE should be considered for stage III pancreatic cancer and inoperable recurrent disease after previous local treatment. Absolute contraindications are ventricular arrhythmias, implantable stimulation devices, congestive heart failure NYHA class 4, and severe ascites. The inter-electrode distance should be 10 to 20 mm and the exposure length should be 15 mm. After 10 test pulses, 90 treatment pulses of 1,500 V/cm should be delivered continuously, with a 90-µs pulse length. The first postprocedural contrast-enhanced computed tomography should take place 1 month post-IRE, and then every 3 months. This article provides expert recommendations regarding patient selection, procedure, and follow-up for IRE treatment in pancreatic malignancies through a modified Delphi consensus study. Future studies should define the maximum tumor diameter, response evaluation criteria, and the optimal number of preoperative FOLFIRINOX cycles.
Keywords: irreversible electroporation; pancreatic tumors; modified Delphi technique; interventional radiology